2004
DOI: 10.1128/aem.70.9.5441-5446.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atomic Force Microscopy Interaction Forces between Bacteria and Silicon Nitride Substrata for Three Commonly Used Immobilization Methods

Abstract: Atomic force microscopy (AFM) has emerged as a powerful technique for mapping the surface morphology of biological specimens, including bacterial cells. Besides creating topographic images, AFM enables us to probe both physicochemical and mechanical properties of bacterial cell surfaces on a nanometer scale. For AFM, bacterial cells need to be firmly anchored to a substratum surface in order to withstand the friction forces from the silicon nitride tip. Different strategies for the immobilization of bacteria h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 29 publications
5
78
0
1
Order By: Relevance
“…An important requirement for AFM investigations is that the sample must be immobilized on a surface. For this purpose, an aliquot of the bacterial suspension of ϳ10 5 cells per ml was allowed to adhere through electrostatic interaction to a poly-L-lysine-coated glass substrate that was prepared as previously described (29). After 15 min, the bacterium-coated glass substrate was rinsed with deionized water to remove loosely attached bacteria and then transferred to the AFM for immediate measurement.…”
Section: Methodsmentioning
confidence: 99%
“…An important requirement for AFM investigations is that the sample must be immobilized on a surface. For this purpose, an aliquot of the bacterial suspension of ϳ10 5 cells per ml was allowed to adhere through electrostatic interaction to a poly-L-lysine-coated glass substrate that was prepared as previously described (29). After 15 min, the bacterium-coated glass substrate was rinsed with deionized water to remove loosely attached bacteria and then transferred to the AFM for immediate measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Vadillo-Rodriguez et al [973] found an increase of adhesion on the 100 s timescale for Streptococcus thermophilus and Boonaert et al [974] observed an increase in adhesion with load for L. lactis bacteria. Another complication can arise from physicochemical and mechanical changes of the cell surface by cell immobilization [975].…”
Section: Cell and Animal Adhesionmentioning
confidence: 99%
“…It can provide three-dimensional images of the surface ultrastructure with molecular resolution, in real time, with minimal sample preparation and experiments can be executed under physiological conditions. Mild treatment of biological samples minimizes artifacts in images or force measurements [31,[35][36][37]. More importantly, imaging and force measurements can be carried out in buffer solutions representative of natural biological environments [35], thus providing new insights into the structure-functional relationship of microbial surfaces.…”
Section: Introductionmentioning
confidence: 99%